THE STUDENTS’ PERCEPTION OF SELF-DIRECTED DIALOGUE IN IMPROVING ENGLISH SPEAKING SKILL AT ENGLISH DEPARTMENT EDUCATION OF UNIVERSITAS MUHAMMADIYAH MAKASSAR - Supriyanto, Andi Muhammad Fiqri; Baso, Farisha Andi; Hijrah (FKIP Unismuh Makassar, 2024)
This study aimed to look for the students' perception of self-directed dialogue in English speaking skill precisely in terms of fluency and vocabulary. The subjects of this study were fourth-semester students of the English Education Depatment, Faculty of Teacher Training and Education, Universitas Muhammadiyah Makassar. The study used interview as an instrument to obtain data in this study.The results of this study showed that self-directed dialogue is effective in improving the students’ English speaking skill in terms of fluency and vocabulary. It was shown when the students had much time to practice with their pairs and tried sharing their knowledge regarding English speaking skill each other. There were no such hardships that students encountered in the process of self-directed dialogue. Correspondingly, students found this learning method positive and engaging.